Influence of Prefabrication on Job Satisfaction in The Construction Industry - Lauren Chandler; Riza Yosia Sunindijo (Institute of Research and Community Outreach - Petra Christian University, 2024)
New construction approaches, such as prefabrication, have been increasingly recognised as a strategy to boost productivity and support the industry’s sustainability and growth. Advancing existing understanding on the benefits of prefabrication to promote its adoption, this research aims to assess job satisfaction and work conditions of construction practitioners involved in prefabrication and assess its impacts on their job satisfaction, represented by job demands, job support, physical work environments, and job perception. Quantitative data were collected from 37 practitioners exposed to prefabrication and 30 practitioners involved in conventional construction. The findings show that prefabrication can lead to higher job satisfaction and better work conditions than conventional construction. Compared with conventional construction, practitioners working in prefabricated projects experienced improved workload distribution, better physical surroundings, and positive job perception. This research, therefore, provides new insights into the benefits of prefabrication and its potential to promote better mental wellbeing and higher productivity.